Russia’s great power imaginary and pursuit of digital multipolarity - Stanislav Budnitsky (Internet Policy Review)
Over the past two decades, Russia has championed the primacy of national governments in managing the global internet. Scholars attribute Russia’s global internet governance philosophy and practices predominantly to its increasingly authoritarian and illiberal regime under President Vladimir Putin. This article, by contrast, explores how Russian ruling elites’ view of Russia as an immutable great power has directed the subsequent Russian governments’ pursuit of a state-based multipolar digital order. To illuminate cultural continuities in Russia’s approach to global communication governance in the post-Soviet period, I examine its state-centric policymaking initiatives at the International Telecommunication Union and the United Nations in the 1990s.